EFFECT OF HIRA PROTEIN ON TRANSCRIPTIONAL REGULATIONS OF GENES IN VERTEBRATE CELLS - Ahyar Ahmad (Universitas Gadjah Mada, 2008)
For better understanding of DNA replicating-coupled chromatin assembly and transcription regulation in eukaryotes, we studied biochemical and genetic analysis of nuclear-related proteins from chicken DT40 cell lines. The genetic analysis of some nuclear proteins, such as HIRA and CAF-1, indicated that these proteins could play overlapping roles in chromatin dynamics and is consistent with the finding that HIRA protein exhibited binding ability to histones and ASF-1, as also ASF-1 bound directly with CAF-1p60. In this study, revealed not only that the N-terminal and C-terminal halves of HIRA mediate individually transcription repressions but also that even one of the seven WD dipeptide motifs and the LXXLL motif of HIRA are required for these mediations in vivo. Finally, we found that HIRA-mediated repression is sensitive to tricostatin TSA and it co-represses transcription together with HDAC-2. We believe our findings will contribute to a major break-through in future studies on the specific, individual roles of HIRA involved in numerous DNA-utilizing processes, through the formation and/or maintenance of the chromatin structure in vertebrate cells.